Marketing Channels, Margin and Farmer Share, and The Marketing Mix of Stingless Bee Honey in North Sumatra, Indonesia: A Field Survey - Harmain, Ummu; Saragih, Jef Rudiantho; Martial, Tri (Universitas Panji Sakti, 2025)
The uniqueness of stingless bee honey makes it an attractive choice as both food and natural medicine for honey consumers, who were previously dominated by honey produced by honeybees (Apis mellifera). This study examines the marketing of stingless bee honey in North Sumatra. The objectives were to determine marketing channels and functions, farmer share, share margin, and the marketing mix. This study uses a cross-sectional survey in five districts/cities in North Sumatra. Respondents were selected using the purposive sampling method (11 stingless bee farmers with at least 50 colonies and at least 5 years of experience), snowball sampling (5 resellers) by recording buying and selling prices. The study results show that three marketing channels are used, with farmers sharing 64.6% on channel 2, yielding an average margin of IDR 106,088/kg. This study found that the longer the distribution chain, the smaller the proportion of income received by farmers (farmer share). Direct channels provide full margins to farmers, whereas the involvement of resellers significantly reduces the farmer's share of the profit. The implications of these findings underscore the importance of developing more efficient and equitable marketing strategies for farmers, including the effective use of digital platforms to expand their markets. However, this study was limited to a specific region and sample. Further studies are recommended to analyze channel efficiency and the impact of digital promotions on increasing sales and farmer welfare.